Health Analysis and Degree of Health of Mobile Fish Sellers - Wa Ode Sifatu; Laxmi; Ruwiah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe the condition of physical health according to their own views as an effect of their daily activities walking to sell fish from aisle to aisle and from house to house. The theory for reading the research data is Stack's 1974 thinking about organizing to address the problems faced by women with qualitative research methods. The results of the study show that the cultural duties of Muna women, namely managing the household and educating children at home, have changed as a result of urbanization in Kendari City. The cultural duties of managing the household and educating children are still being carried out. The organization is that when they leave the house to sell fish, the task of taking care of the children is entrusted to the people at home or to the family closest to the house. They did not experience serious illness, let alone hinder the activity of selling fish around in Kendari City. In general, children's education can be funded up to a bachelor's degree. The only ailments experienced were aches and headaches which were treated with traditional medicine and adequate intake. Unintentionally, the job of selling fish around the junjung in Kendari City has a positive effect on their health, both those who are classified as elderly and not elderly.